(untitled) (Research, Society and Development, 2020)
In this article we focus on the magazine Vozes de Petrópolis, published between 1907 and 2003, one of the primary sources of the research line Rastros: Franciscan cultural heritage and education. It aims to analyze and disseminate the potential of a primary source, edited by the Franciscans, to research on the memory of the presence of these religious brothers in the history of Brazilian education. In the first paragraph of the issue that inaugurated the publications of Vozes de Petrópolis magazine in July 1907, we highlight the basic aspects of this research. Basic aspects inherent to the way in which Vozes de Petrópolis magazine was read and read by schoolchildren, one of the objects of investigation regarding the memory of Franciscans in Brazilian education. With a focus on impact and relevance, be it social, economic, regional or national, the research privileges, through the magazine Vozes de Petrópolis, the memories of Franciscans in Brazilian education, as well as the proposal for a proposed civilizing and moral reading to the public. In view of this, we spoke with Thompson (1998) who proposes a method of producing historical knowledge. We also placed Vozes de Petrópolis magazine on the backing of Benjamin’s (2012) historical-social contributions, the history of reading with Chartier (1990 and 2002) and Darnton (1992 and 2010), the presence of Franciscans in the history of Brazilian education with Röwer (1947) and Sinzig (1910), among others. The results focus on some of the editorial strategies adopted by the Franciscans in contrast to literary and school productions not aligned with the prerogatives of the Catholic Church of the period.